Faktor-Faktor Penentu Keputusan Etis Konsultan Pajak di PT Mitra Manajemen Internasional - Amalia Anan Tasiah; Ratnawati , Dyah (MES Management Journal, 2024)
Ethics is very important in the business world, business ethics refers to the principles and values ​​that influence a company's actions and decision making. As an important part of tax compliance, tax consultants must understand tax regulations and make decisions in accordance with ethics to maintain the integrity of the profession and public trust. A number of large cases of tax evasion and bribery show that tax consultants engage in unethical actions, which can hinder business growth. Tax consultants are responsible for providing tax input in accordance with regulations and liaising with the tax authorities. The difference in interests between consultants and clients causes ethical conflicts. PT Mitra Manajemen Internasional uses policies that support the ethical decision making of tax consultants. This research aims to find factors that influence the ethical decisions of tax consultants at PT Mitra Manajemen Internasional. It is hoped that this research can provide deeper insight and help develop better policies and programs to support ethics in the tax consultant profession through interviews and participant observation.